Evaluation of role of preoperative chemotherapy for carcinoma of the gastro-esophageal junction - El-Kased, Ahmed F.; Abdelbary, Naser M.; Albatanony, Ayman A.; Almelegi, Mohamed H.; Youssef, Fatma I. (International Surgery Journal, 2021)
Background: Preoperative chemotherapy has become an established management of locally advanced carcinoma of gastro-esophageal junction. Determining the down staging effect and predicting the pathological response to preoperative chemotherapy are mandatory. Methods: This is a prospective study which started by 40 patients presenting with gastro-esophageal junction (GEJ) tumor to the General surgery and Oncology outpatient clinics of the Menoufia University Hospitals during the period from July 2017 to July 2020. Pretreatment staging and multidisciplinary group discussion were done for all patients. Inclusion criteria were patients with locally advanced GEJ carcinoma, performance status≤2 and no previous history of chemo or radiotherapies. We excluded patients with distant metastasis, performance state>2 and previous chemo or radiotherapies. Preoperative chemotherapy ECX regimen (epirubicin, cisplatin, capecitabine) was planned. Only 20 patients completed chemotherapeutic regimen for 3 to 4 cycles followed by a radical surgery. All patients were allocated a clinical stage before and after preoperative chemotherapy and were compared to post-operative pathological stage. Postoperative complications were recorded. Follow up of patients was done for 2 years. Results: Among total number of 40 patients, only 20 patients completed our study by preoperative ECX chemotherapy followed by radical surgery. The median overall survival was 30 months and the 2-year disease free survival ranged from 24-40 months with median time of 25.5 months. Complete pathological response was found in 6 patients (30%). Conclusions: Pre-operative chemotherapy using ECX regimen followed by surgery could be used for treatment of locally advanced GEJ carcinoma and has showed a favourable survival.